Unraveling the complexity of the molecular pathways associated with polycystic ovary syndrome (PCOS) and identifying molecular targets for therapeutic development: a review of literature - Akeem Babatunde Sikiru; Muibat Adesola Adeniran; Karimot Akinola; Himanshu Behera; G. Kalaignazhal; Stephen Sunday Acheneje Egena (Middle East Fertility Society Journal, 2023)
Abstract Background Polycystic ovary syndrome (PCOS) is the most typical endocrine disorder affecting women worldwide. Although the etiology of PCOS is not fully understood, genetic factors are believed to play an essential role in its pathogenesis. Hence, this paper presents a review of the outcome of functional enrichment analysis of pathways associated with PCOS phenotypes for the identification of potential molecular targets as area of further research for therapeutic development for PCOS. Method It is the implementation of comprehensive literature search in database including PubMed and Google Scholar and functional analysis of genes including the HSD3B2, PPARG, PPP1R3A, LMNA, and AMH and their roles in the metabolic pathways associated with PCOS. Findings The genes including HSD3B2, PPARG, and LMNA emerged as the most important genes in relation to PCOS, suggesting that they could play key roles in regulating different aspects of PCOS pathogenesis. These findings provide valuable insights into the molecular mechanisms that underlie the complex condition of PCOS and highlight the potential of targeting these genes and their specific pathways as a promising approach to developing effective treatments for PCOS. Conclusion It was concluded that these exploring pathways associated with these genes could provide new insights into the genetic factors contributing to PCOS, and the study recommended further research on these targets for improving the health and quality of life women battling with PCOS worldwide.